A New Taraxastane‐Type Triterpene from Vitex trifolia var. simplicifolia. Issue 11 (November 2013) - Huang, Ming‐Yu; Zhong, Lin‐Jing; Xie, Jie‐Ming; Wang, Fei; Zhang, Yong‐Hong
Abstract 3‐Oxotaraxer‐14‐en‐30‐al (1), a new taraxastane‐type triterpene, together with 14 known compounds, taraxerone (2), 3‐epiursolic acid (3), 2α, 3β‐dihydroxyurs‐12‐en‐28‐oic acid (4), lupeol (5), betulinic acid (6), casticin (7), artemetin (8), luteolin (9), 4‐hydroxybenzoic acid (10), docosanoic acid (11), tetracosanoic acid (12), cerotic acid (13), β‐sitosterol (14), and β‐daucosterol (15), was isolated from the leaves and twigs of Vitex trifolia var. simplicifolia . Compounds 2–6 were found for the first time in this plant. Their structures were established by spectroscopic analysis, including 2D‐NMR techniques. Cytotoxic activities of compounds 3, and 5–10 were tested on the three cancer cell lines, PANC‐1, K562, and BxPC‐3. Results revealed that 7 exhibited cytotoxicity against PANC‐1, K562, and BxPC‐3, with IC50 values of 4.67, 0.72, and 4.01 μg/ml, respectively, whereas 8 was inactive against these cancer cell lines. The structureactivity relationship of compound 7 and 8 indicated that the 3′‐OH group in polymethoxyflavonoids is essential for antitumor activity.